The Role of Islamic Values ​​in Building a Generation of Noble Morals - Ramadhan, Gilang Fuji; Supriatna, Encup (UIN Sunan Gunung Djati Bandung, 2025)
This study explores the role of Islamic values in shaping a morally upright generation, emphasizing the integration of character education within family, school, and community settings. Utilizing a qualitative descriptive approach through library research, this study examines various scholarly sources, including the Qur'an, Hadith, academic books, journal articles, and official documents. Data were analyzed using content analysis to assess the conceptual foundations of Islamic values, strategies for character formation, and their practical applications in social life. The findings reveal that Islamic values play a crucial role in fostering individuals with strong integrity, responsibility, and high moral awareness. Islam provides a balanced approach between encouragement (bashiran) and warning (nazhiran), shaping individuals' consciousness of the consequences of their actions. The study further highlights that character education based on Islamic teachings is highly effective in producing individuals who are not only intellectually capable but also spiritually resilient. As contemporary society faces increasing moral challenges due to globalization and technological advancements, this research underscores the relevance of Islamic character education in addressing these issues. The study concludes that through strong collaboration between families, educational institutions, and society, Islamic values can be effectively implemented to cultivate a generation that is morally grounded and contributes to a harmonious society. The significance of this research lies in its comprehensive analysis of Islamic character education and its practical recommendations for integrating Islamic principles into modern education systems.